2020
DOI: 10.1002/cctc.201901857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Matching Facet Pairs of TiO2 on Photoelectrochemical Water Splitting Behaviors

Abstract: Engineering crystal facets have been proved as one of the most promising strategies for promoting photocatalytic performance of titanium dioxide (TiO2). The earlier research in this field focused on trying to obtain as high ratio of the high energy {001} facet as possible, while later found that the co‐existence of facets is more beneficial. However, controlling crystals to expose suitable facet pairs and facet ratios remains challenging. In this work, we not only comprehensively match possible low‐index facet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Among semiconductor photocatalysts, titanium dioxide (TiO 2 ) has been widely used in photocatalytic degradation of pollutants because of its respectable photocatalytic properties, chemical and biological inertness, no secondary pollution, and low cost [ 6 , 11 ]. There have been numerous reports about using TiO 2 and its composites in various photocatalytic environmental remediations such as waste degradation [ 1 , 11 , 12 , 13 ], water and air purification [ 7 , 11 , 14 ], carbon dioxide reduction [ 15 , 16 , 17 , 18 ], conversion of biomass-derived wastes to valuable chemicals [ 19 , 20 , 21 ], and photocatalytic water splitting for alternative hydrogen energy [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, the main drawbacks of unmodified TiO 2 are the undesirable recombination of electrons and holes, the low efficiency under visible light irradiation, and the limited adsorption of dyes on the catalyst’s surface.…”
Section: Introductionmentioning
confidence: 99%
“…Among semiconductor photocatalysts, titanium dioxide (TiO 2 ) has been widely used in photocatalytic degradation of pollutants because of its respectable photocatalytic properties, chemical and biological inertness, no secondary pollution, and low cost [ 6 , 11 ]. There have been numerous reports about using TiO 2 and its composites in various photocatalytic environmental remediations such as waste degradation [ 1 , 11 , 12 , 13 ], water and air purification [ 7 , 11 , 14 ], carbon dioxide reduction [ 15 , 16 , 17 , 18 ], conversion of biomass-derived wastes to valuable chemicals [ 19 , 20 , 21 ], and photocatalytic water splitting for alternative hydrogen energy [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, the main drawbacks of unmodified TiO 2 are the undesirable recombination of electrons and holes, the low efficiency under visible light irradiation, and the limited adsorption of dyes on the catalyst’s surface.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of photoanode have been used in PEC water splitting reactions, such as titanium dioxide (TiO 2 ), [2][3][4] graphitic carbon nitride (gÀ C 3 N 4 ), [5][6][7] and heterojunction catalysts. [8][9] Particularly, TiO 2 has been used extensively due to its high chemical/thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14] Owing to the cooperative effect between oxidative and reductive surfaces on the TiO 2 itself, TiO 2 with coexposed {001}-{010} facet has been used as an effective photoanode in solar driven photocatalytic water splitting reactions. [4,15] However, some studies have shown that improvement in PEC performance of the TiO 2 based photocatalyst via incorporation of {001} was not always the case. [4,13] The discrepancies depend on the ratio of {001} compared to other facets in the TiO 2 particles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations